Cryo-field emission scanning electron microscopy imaging of a rigid surfactant mesophase - Tan, Grace (Langmuir : the ACS journal of surfaces and colloids, 2008)
The aerosol OT/ L-alpha-phosphatidylcholine/isooctane/water system forms a rigid mesophase that transitions from reverse hexagonal to multilamellar in structure at specific water contents. This study shows that characteristics of ordered liquid-crystalline mesophases can be distinguished and imaged in high clarity using cryo-field emission scanning electron microscopy (cryo-FESEM). The reverse hexagonal phase consists of bundles of long cylinders, some with length scales of over 2 microm, that are randomly oriented as part of a larger domain. Cryo-imaging allows the visualization of the intercylinder spacings and the details of transitions from one domain to another. The multilamellar structured mesophase consists of spherical vesicles of 100 nm to 10 microm in diameter, with intervening noncrystalline isotropic regions. Coexistence regions containing both the reverse hexagonal and lamellar structures are also observed in the transition from the reverse hexagonal to the lamellar phase. These results complement and qualitatively verify our earlier studies with small-angle neutron scattering, high-field nuclear magnetic resonance spectroscopy, and freeze-fracture direct imaging transmission electron microscopy. The information is useful in understanding materials templating in these rigid systems